2011
DOI: 10.1002/poc.1864
|View full text |Cite
|
Sign up to set email alerts
|

Tuning HOMO–LUMO levels: trends leading to the design of 9‐fluorenone scaffolds with predictable electronic and optoelectronic properties

Abstract: Highest occupied molecular orbital-lowest unoccupied molecular orbital (HOMO-LUMO) tuning is an important consideration in the development of organic-based semiconducting materials. A study of the specific effects and overall trends for the HOMO-LUMO tuning of a diverse series of 9-fluorenones by means of extended conjugation and substituent effects is described. Trends were explored in a range of compounds, beginning with structures having highly electron-withdrawing substituents and progressing to structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
47
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 34 publications
8
47
0
5
Order By: Relevance
“…1). [61][62][63][64][65] In the present study, the Hammett constants (σ) increase in the order of methoxy (−0.27) < tert-butyl (−0.20) < trifluoromethyl (+0.54), 26,27 in good agreement with the variation of the observed nanoparticle photoluminescence emissions. As shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“…1). [61][62][63][64][65] In the present study, the Hammett constants (σ) increase in the order of methoxy (−0.27) < tert-butyl (−0.20) < trifluoromethyl (+0.54), 26,27 in good agreement with the variation of the observed nanoparticle photoluminescence emissions. As shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“… [a] E ox is the value of the first peak in the square‐wave voltammograms. [b] The HOMO was determined from the oxidation potential using the relationship HOMO=− e ( E ox −0.234)−4.8 eV, in which +0.234 V is the redox potential for the ferrocene/ferrocenium (Fc/Fc + ) couple measured as an external standard for the system versus a nonaqueous Ag/Ag + reference electrode, − e is a notation indicating the acceleration of one electron through the adjusted potential, and −4.8 eV represents the work function of the Fc/Fc + couple relative to the vacuum level 35. [c] The value of λ onset is taken as the intersection of the spectrum baseline and a line tangential to the edge of the absorption band 35.…”
Section: Resultsmentioning
confidence: 99%
“…6-23 A number of contributions reporting experimental ndings and theoretical calculations on ICT molecules, and more recently, experimental work coupled with quantum chemical calculations have been reported. 22 This band gap tailoring technique has been used by many research groups, [21][22][23][24] for example, for designing efficient polymers 23 and developing organic semiconductor materials. The strength of charge transfer in such systems can be modulated by changing the donor/acceptor strengths and such modulation can lead to tailoring of the band gap as well.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Excited state ICT oen occurs through a p-electron bridge. 24 In a recent contribution, 25 we have experimentally shown that 3-(phenylamino)-2-cyclohexen-1-one (PACO) is an interesting ICT probe with dual uorescence in polar solvents, due to emissions from a locally excited (LE) state and an intramolecular charge transfer (ICT) species with large dipole moment, formed in the excited state. 23 A judicious choice of donor/acceptor units in a molecule could facilitate simultaneous manipulation of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energies, opening up the possibility of tailoring the band gap and hence the properties shaped by the band gap, for example, the colour of the probe.…”
Section: Introductionmentioning
confidence: 99%